2015
DOI: 10.3109/13651501.2015.1082599
|View full text |Cite
|
Sign up to set email alerts
|

Self-selected intensity exercise in the treatment of major depression: A pragmatic RCT

Abstract: We observed a large and clinically significant change in HRSD-17 scores. Moderate changes in BDI-II scores without clinical significance and small changes in physical fitness assessments were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…Several other clinical studies have demonstrated that exercise is highly effective at reducing the clinical symptoms and minimizing the rate of reoccurrence of MDD episodes(Blumenthal et al, 2007;Doose et al, 2015;Dunn et al, 2005). The general consensus among experts remains that more frequent activity over a longer period of time, results in greater efficacy of exercise in the treatment ofMDD (Carek et al, 2011), which is likely due, at least in part, to the inflammation-altering effects of exercise.…”
mentioning
confidence: 95%
“…Several other clinical studies have demonstrated that exercise is highly effective at reducing the clinical symptoms and minimizing the rate of reoccurrence of MDD episodes(Blumenthal et al, 2007;Doose et al, 2015;Dunn et al, 2005). The general consensus among experts remains that more frequent activity over a longer period of time, results in greater efficacy of exercise in the treatment ofMDD (Carek et al, 2011), which is likely due, at least in part, to the inflammation-altering effects of exercise.…”
mentioning
confidence: 95%
“…The important study of Doose et al [36] did not clarify three aspects of the impact of preferred intensity exercise on depression, which are in the scope of the current study. First, Doose et al did not employ the benchmark prescribed-intensity exercise as a direct comparator.…”
Section: Introductionmentioning
confidence: 79%
“…The pragmatic RCT by Doose et al [36] explored the clinical and individual antidepressant effects of an eightweek ideographic preferred intensity exercise model (n = 30) vs. the wait-for-intervention condition (n = 16) in patients diagnosed with a depressive episode. Pre-and post-intervention depression assessed via a self-report outcome [Beck Depression Inventory-II [BDI-II]; 37] showed 36.67, 16.67 and 46.67% of the preferred intensity group with scores consistent with depression recovery, improvement and non-significant change, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effect of PA on depression has been previously studied. Small intervention studies assessing the amelioration of pre-existent depression suggested that physical activity could be beneficial when treating adults with depression, [18] and the Cochrane Collaboration in a 2013 review, concluded that physical activity had clinical effects on depressive patients [19].…”
Section: Introductionmentioning
confidence: 99%